GAMBARAN FAKTOR PERSONAL PENYEBAB KETIDAKBERDAYAAN PENDERITA COVID-19 YANG ISOLASI DI SAFE HOUSE - Priasmoro, Dian Pitaloka; Kurniawan, Satria Bagus (Universitas Tribhuwana Tunggadewi, 2021)
Spread of the new virus 2019-Novel Coronavirus (2019-nCov) has caused a health crisis in the world. This prompted the government to make efforts to handle it by providing temporary isolation places for Covid-19 sufferers in a shelter or safe house to prevent transmission. The long treatment process and symptoms of the disease make the sufferer helpless. This study aims to describe the personal factors that cause helplessness. The research method was descriptive, population was Covid-19 sufferers who are isolated in a Safe House, and sample was some of the patients who experience helplessness as many as 57 respondents. Data were taken from November to December 2020 using google form and then analyzed univariately, presented in the form of a percentage. The results showed that there were personal factors that influenced helplessness, namely 94.7% middle adults ( 26 years), 54.4% highly educated (PT), 89% married, 54, 4% had income above the UMR, and 86% were of the type. male genital. So that each sufferer has different responsibilities towards his family, feels anxious about his illness because of the high morbidity and mortality rates, and cannot work for a long period of time. Based on the results of this study, a continuous program that involves families, officers, and fellow sufferers is needed to increase support.